Tlingit dancers at potlatch with painted boards, Klukwan, Alaska, October 14, 1898 - Pillsbury, Arthur C. (Arthur Clarence)
Men in clearing near tent & small wooden building ready for dance; they wear a variety of headdresses, a number have Chilkat blankets over their shoulders or Chilkat dance shirts, painted faces and rings in their noses. Several hold painted boards, including two that are paddle-shaped and over 6 foot long. Caption on image: Dancers at the Klukwan Potlatch Oct. 14 '98. 424. A C Pillsbury. Copy print made from original at Seattle Public Library